Changes in rock matrix compressibility during deep CO2 storage. Issue 5 (28th July 2021) - Kim, Kiseok; Makhnenko, Roman Y.
Abstract: Geologic carbon storage projects aim to permanently trap large volumes of CO2 in reservoir rock sealed with low permeability layers. As high‐pressure supercritical or liquid CO2 is injected, hydromechanical and chemical processes caused by the reaction between the rock and acidic mixture of brine and CO2 are initiated. The compressibility of reservoir rock needs to be properly characterized in order to assess the deformation and stability of the host formations, and there are a number of factors to be considered, including the matrix structure, solid, pores, and fluid. This study triggers from a fundamental question whether CO2 treatment affects the compressibility of the rock matrix and its dominant composing solid minerals. Three different reservoir representatives are selected: Berea sandstone for silica‐rich rock, and Apulian limestone and Indiana limestone for calcite‐rich rock. Quartz and calcite are the main composing minerals of the reservoir rock, and their crystals are separately examined. Experimental methods are introduced for high‐pressure CO2 treatment of water‐saturated materials, and measurements of the unjacketed and solid compressibilities are conducted. No change in the solid compressibility of the sandstone and quartz after CO2 treatment is observed, whereas it increases by 18–21% for the limestones and by 15% for calcite. The latter observation is inconsistent with the ultrasonic wave velocities measurements and is believed to be due to the local dissolution of the calcite crystal surface. The results show that only the solid matrix of the limestones becomes more compressible after CO2 treatment. Consequent microimaging and mercury intrusion porosimetry analyses allowed observations of dissolution and precipitation of calcite, and creation of new connected and non‐connected pores. Finally, the changes in limestone solid compressibilities and pore structure could significantly affect the rock properties and behavior during and after CO2 injection and should be accounted for in the reservoir models. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.